Perceived Emotional Impact of COVID-19 and Depressive Symptoms among Male Same-Sex Chilean Couples: Direct and Indirect Dyadic Associations through Relationship Satisfaction. Issue 3 (3rd April 2023) - Guzmán-González, Mónica; Barrientos, Jaime; Garrido, Lusmenia; Bahamondes, Joaquín; Gómez, Fabiola; Espinoza-Tapia, Ricardo; Casu, Giulia
Abstract: Stressors arising from the COVID-19 pandemic can spill over into the quality of couple relationships, with negative consequences on mental health. The mental health impact of COVID-19 might be particularly pronounced in disadvantaged populations such as LGBT people. This study aimed to examine direct and indirect dyadic associations between emotional impact of COVID-19 and depressive symptoms through relationship satisfaction in male same-sex couples. Using a cross-sectional design, 158 male same-sex Chilean couples completed self-report measures of the emotional impact of COVID-19, relationship satisfaction and depressive symptoms. We used the actor-partner interdependence mediation model for indistinguishable dyads to explore the direct and indirect dyadic associations. Results indicated that each partner's perceived emotional impact of COVID-19 was associated with his own higher depressive symptoms directly and indirectly, through his own lower relationship satisfaction. The other partner's perceived emotional impact of COVID-19 was associated with one's own higher depressive symptoms only directly. Our findings reinforce the notion that satisfactory couple relationships can act as a protective factor against depression in the LGBT population. Programs to promote adaptive coping strategies to deal with the emotional impact of the COVID-19 pandemic may have beneficial effects for the emotional adjustment of male same-sex couples, also by promoting relationship satisfaction.